Agricultural land use change in Karamoja Region, Uganda. (March 2017) - Nakalembe, Catherine; Dempewolf, Jan; Justice, Christopher
Abstract: We examine dramatic cropland expansion in Karamoja, Uganda by investigating the links between biophysical and political historical events leading to the current state of agricultural land use. Our objective was to quantify agricultural expansion, uncover the dominant drivers leading to the current state of agricultural land use and its impacts on livelihoods. Region wide analysis of remotely sensed data, land use policy and history as well as farmer interviews were undertaken. We posit that government programs instituting sedentary agriculture are the most significant drivers of cropland expansion in Karamoja. We show a 299% increase in cropland area between 2000 and 2011 with most expansion occurring in Moroto District (from 706 ha to 23, 328 ha). We found no evidence of an increase in overall crop production or food security and food aid continues to be essential due to recurrent crop failures. Due to lack of resources for inputs (e.g., seeds and labor) cultivated fields remain very small in size and over 55% of once cultivated land is left fallow. Our findings bring into question whether continued promotion of rain-fed agriculture in Karamoja serves the best interests of the people. Current cropland expansion is directly competing and compromising pasture areas critical for livestock-based livelihoods. Without strong agricultural extension programs and major investments in climate-smart options, cropland expansion will continue to have a net negative impact, especially in the context of current climate projections which indicate a future decrease in rainfall, increase in temperature and an increase in the frequency and magnitude of extreme events.